Optimization of in Vitro Culture of Taro Banana (Musa paradisiaca var. sapientum L.) Based on Thidiazuron: A Foundation for Developing a Biotechnology Booklet to Enhance Decision-Making Skills - Titin Purnaningsih; Kimeni; Yohannes Edi Gunawan; Akhmadi; Nuriman; Chaidir Adam; Silvita; Ririn Fahrina; Ennike Gusti Rahmi (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to optimize the concentration of Thidiazuron (TDZ) in the in vitro culture of taro banana (Musa paradisiaca var. sapientum L.) and to integrate the results as a foundation for developing a biotechnology booklet to enhance decision-making skills. The research was conducted using an experimental method with various TDZ concentration treatments, observing parameters such as the number of shoots and leaves produced. To bridge the gap between biotechnological research and its application in education, this study investigates the optimization of Thidiazuron (TDZ) concentrations for the in vitro multiplication of taro banana (Musa paradisiaca var. sapientum L.). The results showed that the use of TDZ effectively induced shoot formation, with the optimal concentration obtained at 0.01 mg/L TDZ, producing an average of 22.25 shoots and 24.25 leaves. In addition to generating biological data, each stage of this study reflected the implementation of decision-making skills, including problem identification, information gathering, criteria determination, solution selection, and result evaluation. These findings serve as the foundation for developing a biotechnology booklet as a contextual learning medium that not only facilitates the understanding of biotechnology concepts but also trains students to make scientific and reflective decisions.